Regulation of mitochondrial biogenesis by transcriptional coactivators and estrogen-related receptor alpha - Kralli, Anastasia (Henry Stewart Talks, 2007)
Mitochondrial biogenesis, Transcriptional regulation of mitochondrial biogenesis, The roles of transcriptional coactivators of the PGC-1 family and of the orphan nuclear receptor Estrogen-Related Receptor alpha (ERRa) in the regulation of mitochondrial biogenesis, Physiologic function of ERR-alpha-dependent mitochondrial biogenesis
Reviewed at 2016/11/28